Evaluating knowledge and awareness of 3D design and printing among dental students in Saudi Arabia: a cross-sectional study - Alamri, Hamdan; Alshammari, Falah R.; Bin Rahmah, Abdullah; Alsaif, Mohammed I.; Almutairi, Farah; Alolaywi, Hissah; Altariqi, Aroub; Alotaibi, Sarah; Almutairi, Rahaf; Almadhoon, Hossam; AlMoharib, Hani S. (Frontiers in Dental Medicine, 2024)
Introduction As 3D design and printing technology gains popularity, there remains limited evidence on dental students' perceptions in Saudi Arabia regarding its use. This study aims to assess the knowledge and awareness of dental students in Saudi Arabia about 3D design and printing technology. Methods A cross-sectional questionnaire-based study was conducted among dental students in their third, fourth, and fifth years at multiple universities in Saudi Arabia between February and October 2023. A validated self-administered questionnaire with 15 close-ended items, including demographic and knowledge-related questions about 3D design and printing, was used. Statistical analysis was performed using Chi-square and Fisher exact tests to identify factors associated with knowledge and awareness levels. Results A total of 374 dental students participated in the study, with 63.1% being female students. Of the participants, 40.4% identified the cost of equipment as the primary barrier to 3D printing usage in dentistry in Saudi Arabia. The majority (94.4%) recognized the advantages of 3D models for implant placement. Awareness of 3D printing utilization in the field was reported by 69.3% of participants, and 74.3% acknowledged its increasing popularity. Furthermore, 73.8% of participants expressed confidence in the biocompatibility and safety of 3D printed materials. A significant percentage (64.0%) were aware of 3D printing's role in creating Invisalign aligners, and 42.4% believed in the value of 3D printed drill guides for root canal treatment. The study found statistically significant regional differences (p < 0.05) across all questions. Participants primarily relied on colleges (64.8%) as their source of information, and a high proportion (82.4%) expressed interest in further exploring the usage of 3D printing in dentistry. Conclusion Our study found that students' knowledge and awareness in Saudi Arabia are generally satisfactory. Integrating 3D printing into dental curricula and providing workshops is crucial to meet dental students' interest in exploring its usage and equipping them for its future implementation.